Diversity of Zooplankton in Reservoir Faculty of Fisheries and Marine University of Riau - Defi Fitriya Dalimunthe; Asmika Harnalin Simarmata; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThis research was carried out in January-February 2020 in the waters of the Riau University Reservoir. This study aims to determine the diversity of zooplankton in the Faperika Reservoir, Riau University. The method used in this study is a survey method. Sampling of zooplankton is done once a week for three month. Samples were taken from the catch in the afternoon using a plankton net.During the study, there were 20 types of zooplankton consisting of 4 classes, namely Copepoda, Cladocera, Rotifera, Protozoa that live in the waters of the Faperika Reservoir, Riau University. The species found were Cylops sp, Daphnia sp, Nauplius sp, Bosmina sp, Moina sp, Alona sp, Anuraeopsis sp, Branchionus sp, Hexarthra sp, Keratella sp, Polyarthra sp, Tricoccerca sp, Asplanchna sp, Notholca sp, Philodina sp, Agronotholca sp, Macrocaetus sp, AmoebaRadiosa, Cryptomonas sp, Coleps sp. Of all the types of zooplankton found, the Rotifera class was the most common class.The structure of the zooplankton community around the Riau University Fisheries Reservoir is that the zooplankton density is included in the medium category, namely 1600-2250 ind/L, the high zooplankton diversity value is 3.158-3.334, the dominance index ranges from 0.976-0.919, meaning a balanced uniformity index in the Riau University Fisheries Reservoir.Keywords:Community, Diversity, Dominance,Water Quality, Zooplankton,